Therapeutic Potentials of Selected Antihypertensive Agents and Their Fixed-Dose Combinations Against Trastuzumab-Mediated Cardiotoxicity - Olorundare, Olufunke Esan; Adeneye, Adejuwon Adewale; Akinsola, Akinyele Olubiyi; Ajayi, Abayomi Mayowa; Agede, Olalekan Ayodele; Soyemi, Sunday Sokunle; Mgbehoma, Alban Ikenna; Okoye, Ikechukwu Innocent; Albrecht, Ralph M.; Ntambi, James Mukasa; Crooks, Peter Anthony (Frontiers in Pharmacology, 2021)
Trastuzumab (TZM) is useful in the clinical management of HER2-positive metastatic breast, gastric, and colorectal carcinoma but has been limited by its off-target cardiotoxicity. This study investigates the therapeutic potentials of 0.25 mg/kg/day amlodipine, 0.035 mg/kg/day lisinopril, 5 mg/kg/day valsartan and their fixed-dose combinations in TZM-intoxicated Wistar rats that were randomly allotted into 10 groups of 6 rats for each group. Group I rats were treated with 10 ml/kg/day sterile water orally and 1 ml/kg/day sterile water intraperitoneally; Group II, III and IV rats were orally gavaged with 5 mg/kg/day valsartan and 1 ml/kg/day sterile water intrapeitoneally, 0.25 mg/kg/day amlodipine and 1 ml/kg/day sterile water intraperitoneal route, 0.035 mg/kg/day lisinopril and 1 ml/kg/day sterile water administered intraperitoneally, respectively. Group V rats were orally treated with 10 ml/kg/day of sterile water prior to intraperitoneal administration of 2.25 mg/kg/day of TZM. Groups VI-VIII rats were equally pretreated with 5 mg/kg/day valsartan, 0.25 mg/kg/day amlodipine, and 0.035 mg/kg/day lisinopril before intraperitoneal 2.25 mg/kg/day TZM treatment, respectively; Groups IX and X rats were orally pretreated with the fixed-dose combinations of 0.25 mg/kg/day amlodipine + 0.035 mg/kg/day lisinopril and 5 mg/kg/day valsartan + 0.035 mg/kg/day lisinopril, respectively, before TZM treatment. Cardiac injury and tissue oxidative stress markers, complete lipids profile, histopathological and immunohistochemical assays were the evaluating endpoints. Results showed that repeated TZM treatments caused profound increases in the serum TG and VLDL-c levels, serum cTnI and LDH levels, and cardiac tissue caspase-3 and -9 levels but decreased BCL-2 expression. TZM also profoundly attenuated CAT, SOD, GST and GPx activities and increased MDA levels in the treated tissues. In addition, TZM cardiotoxicity was characterized by marked vascular and cardiomyocyte congestion and coronary artery microthrombi formation. However, the altered biochemical, histopathological and immunohistochemical changes were reversed with amlodipine, lisinopril, valsartan and fixed-dosed combinations although fixed-dose valsartan/lisinopril combination was further associated with hyperlipidemia and increased AI and CRI values and coronary artery cartilaginous metaplasia. Thus, the promising therapeutic potentials of amlodipine, lisinopril, valsartan and their fixed-dose combinations in the management of TZM cardiotoxicity, majorly mediated via antiapoptotic and oxidative stress inhibition mechanisms were unveiled through this study.